A COMPARATIVE STUDY OF ANTIBACTERIAL, ANTIOXIDANT ACTIVITY AND TOTAL CONTENT OF PHENOLIC COMPOUNDS FROM A COMBINATION OF CLOVE AND CINNAMON ESSENTIAL OILS - SAFITRI, META; SULISTYANI, NANIK; WAHYUNINGSIH, IIS; SYLVIA, DIANA; APRILLIANI, ARINI (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to identify the right combination of Clove Flower Essential Oil (CFEO) and Cinnamon Essential Oil (CEO) that has the potential to be used as a medicine for diabetic wounds. Methods: Antibacterial activity against Staphylococcus aureus was observed using the paper disc method. Antioxidant activity was examined the DPPH (2.2-Diphenyl-1-Picrylhydrazyl acid) method. Phenol content was tested using the Folin Ciocalteau method. Results: The results showed that the antibacterial activity of CFEO was lower than that of CEO in a single form. The combination of CFEO: CEO was made with varied concentrations of 1.25; 2.5; and 5%. Each concentration has the following ratios (1:1), (1:2), (1:3), (2:1), and (3:1). The highest antibacterial activity was found at a concentration of 5% combination (1:3) with an average inhibition zone diameter of 20.61±1.07. The minimum inhibitory concentrations of CFEO, CEO, and the combination of CFEO: CEO (1:3) against Staphylococcus aureus bacteria were 0.078%, 0.046%, and (0.0195:0.0935%). The antioxidant activity of the CFEO: CEO (3:1) combination showed the highest antioxidant activity with an IC50 of 42,706 ppm. Single CFEO showed had a higher phenol content of 548.065 mgGAE/g compared to single CEO. The combination CFEO: CEO (3:1) showed the highest phenol content of 262,473 mgGAE/g compared to combination (1:1) and (1:3). Conclusion: Based on the results, the combination of CFEO and CEO (3:1) has the highest antibacterial activity, antioxidant and phenol content. Therefore, it can be proposed as an active ingredient for diabetic wound preparation.